Jennifer : an O'Malley love story - Henderson, Dee (Henderson, Dee. O'Malley series., 2013)
"After finding God and falling in love, life is good for Dr. Jennifer O'Malley. But can her faith--and her family--survive the challenges ahead?"--Provided by publisher.